Outcome and treatment quality of transfer primary percutaneous intervention in older patients with acute ST-elevation myocardial infarction (STEMI) - Birkemeyer, Ralf; Rillig, Andreas; Treusch, Fabian; Kunze, Markus; Meyerfeldt, Udo; Miljak, Tomislav; Kostin, Daniel; Koch, Annette; Jung, Werner; Oster, Peter; Bahrmann, Anke (Archives of gerontology and geriatrics, 2011)
The aim of this study was to evaluate the outcome and treatment quality of transfer percutaneous coronary intervention (PCI) in older patients with acute STEMI. In this prospective study all patients with diagnosed acute (pain-to-balloon≤12h) STEMI transferred to our institution for primary PCI (n=400) between January 2005 and October 2007 were under investigation. Overall 125 older patients with age ≥70 years were included (mean age 77.5±4.9 years; 77 males). Pre-hospital delays were more common in older patients with longer pain-to-balloon: median (range)=85 (5-629) vs. 66 (1-688) p=0.031, and pain-to-first medical-contact-times: median: 206 (84-711) vs. 172 (45-720); p=0.001. A trend towards a higher (non-significant) rate of major 5/125 (5%) vs. 5/275 (1.8%), p=0.195 and minor 10/125 (8%) vs. 14/275 (5.1%). p=0.256 bleeding complications in older patients was evident. In-hospital mortality was significantly higher in older patients compared to the younger patients group: 13/125, 10.4% vs. 8/275, 2.9%, p=0.002). Overall mortality at 30-day follow-up was 11.2% in older and 3.3% in younger patients: 14/125 vs. 9/275, p=0.002. Transfer PCI is an effective treatment strategy for older patients with acute ST-elevation myocardial infarction. Overall-30-day mortality in older STEMI-patients transferred for primary PCI is comparably low.